Pengaruh Penggunaan Campur Kode dalam Pembelajaran Terhadap Kemampuan Menulis Bahasa Indonesia Siswa Kelas VII di SMP Negeri 1 Pademawu Tahun Pelajaran 2017/2018 - Ainur Rofiq Hafsi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The use of mixed code in learning can create a communicative atmosphere and students easily understand the subject matter delivered. This study aims to prove the influence of mixed code usage in learning on the Indonesian language writing skills of class VIII students at Pademawu 1 Public High School year 2017/2019. Data collection techniques in this study used tests. Data analysis in this study uses a statistical analysis method in the form of a test. The result of tcount = 2.213 which is then consulted with ttable. With dk = (32 + 31-2) = 61 obtained ttable at significant level 5 & is 1.671. From this value it appears that t count> t table is 2,213> 1,671. This means that H1 is accepted and H0 is rejected. The results of this study can be concluded